Major Components of Crm For the Banking Industry: A comprehensive analysis of CRM components in the banking industry (Journal of Advances and Scholarly Researches in Allied Education, 2013)
We highlighted the problems associated with the currentuse of CRM within the banking industry. Multiple contact channels of banks suchas branch banking, phone banking, ATM, and internet banking are also discussed.Then, major components of CRM that are commonly used at bank’s contact channelsand at bank’s internal operational departments are thoroughly presented. Thesecomponents are categorized based on the designed taxonomy comprises of severalCRM components that are classified into four major operational areas of a banki.e., (i) Marketing, (ii) Sales, (iii) Service  and  Support, and (iv)  IT  and IS.  Ideally, in banks, CRM isimplemented across these four operational areas. CRM components in each areaare thoroughly presented.